2010
DOI: 10.1152/ajpregu.00096.2010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity to acute angiotensin II is testosterone dependent in adult male growth-restricted offspring

Abstract: cental insufficiency results in intrauterine growth restriction (IUGR) and hypertension in adult male growth-restricted rats. Although renal ANG II and plasma renin activity do not differ between growthrestricted and control rats, blockade of the renin-angiotensin system (RAS) abolishes hypertension in growth-restricted rats, suggesting that the RAS contributes to IUGR-induced hypertension. Moreover, castration abolishes hypertension in growth-restricted rats, indicating an important role for testosterone. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 32 publications
6
62
0
Order By: Relevance
“…This finding suggests that the enhanced responsiveness to Ang II in female protein-restricted rats is testosterone dependent and, importantly, indicates that involvement of the RAS in prenatal protein restriction-induced hypertension may necessitate modulation by testosterone. Similar responses of testosterone-dependent enhancement in responsiveness to Ang II is observed in adult growth-restricted male rats born to pregnant rats with reduced uterine perfusion [28].…”
Section: Sathishkumar Et Alsupporting
confidence: 64%
“…This finding suggests that the enhanced responsiveness to Ang II in female protein-restricted rats is testosterone dependent and, importantly, indicates that involvement of the RAS in prenatal protein restriction-induced hypertension may necessitate modulation by testosterone. Similar responses of testosterone-dependent enhancement in responsiveness to Ang II is observed in adult growth-restricted male rats born to pregnant rats with reduced uterine perfusion [28].…”
Section: Sathishkumar Et Alsupporting
confidence: 64%
“…[1][2][3][4][5] This steroid hormone contributes not only to the development of arterial hypertension but also to hypertensionassociated vascular and renal abnormalities. 6 In humans, it is still controversial whether testosterone contributes to or protects from cardiovascular disease. Although many reports indicate that low testosterone levels are associated with high risk of cardiovascular disease and that testosterone replacement improves cardiovascular and metabolic functions, [7][8][9] other studies indicate that older men with higher testosterone levels are more likely to have cardiovascular disease.…”
mentioning
confidence: 99%
“…In addition, some reports of animal studies have shown that intrauterine growth-restricted offspring exhibited an enhanced sensitivity to angiotensin in spite of normal expressions of intrarenal angiotensin. 26,27 RAA activation in the pathogenesis of TTTS may be applied not only to TTTS patients, but also to MD twins with BW discordance and with selective intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 99%